Productivity of Loessal Grasslands in the Kluane Lake Region, Yukon Territory, and the Beringian "Production Paradox" - Laxton, N.F.; Burn, C.R.; Smith, C.A.S. (ARCTIC, 1996)
The Beringian "Production Paradox" is posed by abundant evidence that large ungulates populated unglaciated portions of northwestern North America and adjacent northeast Asia during the late Pleistocene, while botanical data from the same period suggest a poorly productive tundra environment. It is not clear how the large animals sustained themselves, but portions of Beringia, locally in receipt of loess, may have harbored sufficient forage-producing plants to nourish these animals. Loessal soils in the region today are warm and dry in summer, and are often used as rangelands. The loessal hypothesis was examined on grasslands in the Kluane Lake area, southwest Yukon Territory, at sites which have recently received loess blown from the Slims River delta. The biomass and species diversity of grasslands around the lake increase with the quantity of silt in the soil. Likewise, soil fertility indices, including total nitrogen, available nitrogen (NH4), and total carbon, increase with silt content, particularly at sites where the soil surface has been stable for some time, and a "humified" loess (Ahk) horizon has developed. These results support the hypothesis that sites in receipt of loess may have played a significant role in the vegetative productivity of the Beringian ecosystem. Le paradoxe de production Béringien signale que de nombreux indices témoignent de la présence de larges ongulés dans des régions non-glaciées du nord-ouest de l'Amérique du Nord et du nord-est de l'Asie adjacente durant le Pléistocène supérieur, alors que des données botaniques datant de la même époque suggèrent l'existence d'une toundra peu productive. Comment d'aussi larges animaux ont pu subvenir à leurs besoins n'est pas absolument clair mais certaines portions de la Béringie recevant des apports en loess ont pu récéler suffisamment de plantes fourragères pour les nourrir. Aujourd'hui, les sols loessiques de la région sont chauds et secs durant l'été et sont souvent utilisés comme pâturages. L'hypothèse loessique est examinée pour ...